Analysis of OJT Implementation Standardization on Radar ATC Trainee Competence at AirNav Indonesia Palembang - Fuad Anwar; Rany Adiliawijaya; Lina Rosmayanti (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the effect of the standardization of On-the-Job Training (OJT) implementation for Air Traffic Controllers on the competency of Radar OJT participants at Perum LPPNPI Palembang Branch. A quantitative research approach was employed to examine the relationship between OJT standardization as the independent variable and participant competency as the dependent variable. The research sample consisted of 57 respondents selected using a total sampling technique to ensure comprehensive representation. Data were collected through structured questionnaires that had been tested for validity and reliability, and subsequently analyzed using SPSS version 26. The results of the validity test confirmed that all questionnaire items were valid, while reliability testing showed high Cronbach’s Alpha values for both the OJT standardization and competency variables, indicating strong internal consistency. Correlation analysis revealed a very strong relationship between OJT implementation standardization and Radar OJT participant competency. Furthermore, simple linear regression analysis demonstrated that OJT standardization contributed substantially to the improvement of participant competency.